Antibacterial Activity of Indonesian Medicinal Plant Extracts Tinospora crispa, Averrhoa bilimbi and Syzygium polyanthum against Shigella sonnei - Laili Fitri Yeni; Nurfatehah; Erma; Eni Eka Sari (Postgraduate, University of Mataram, 2025)
Diarrhea and dysentery are major health problems in Indonesia, with Shigella sonnei being one of the primary causative agents. Excessive use of antibiotics has led to bacterial resistance, necessitating safe and effective alternative treatments. This study evaluates the antibacterial potential of extracts from brotowali (Tinospora crispa), wuluh starfruit (Averrhoa bilimbi), and bay leaf (Syzygium polyanthum) against Shigella sonnei. Plant materials were sourced from Kakap Village, West Kalimantan, and extracted using maceration with 96% ethanol. Phytochemical tests were conducted to identify active compounds in the extracts, while antibacterial activity was assessed using the disk diffusion method at extract concentrations of 20%, 40%, 60%, and 80%. All three plant extracts contained active compounds such as alkaloids, flavonoids, phenolics, and tannins. Antibacterial tests showed that all extracts exhibited antibacterial activity against S. sonnei, with bay leaf extract at 80% concentration demonstrating the largest inhibition zone of 20.3 mm. Statistical analysis indicated that increasing extract concentration enhanced antibacterial effectiveness. This study suggests that extracts of brotowali, wuluh starfruit, and bay leaf have the potential to be effective natural antibacterial agents against S. sonnei. Further research should focus on understanding the mechanisms of action and exploring the potential clinical applications of these plant extracts. Additionally, integrating these findings into science education can enhance students' scientific literacy and provide practical examples of using natural resources in addressing health issues.